All Days 2012
DOI: 10.2118/159683-ms
|View full text |Cite
|
Sign up to set email alerts
|

Has the Economic Stage Count Been Reached in the Bakken Shale?

Abstract: The Bakken is one of the most active basins in the world in terms of number of rigs, with over 200 operating on the US side of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Engineering studies focused on improving well productivity by adjusting well completion design factors. An early study by Baihly et al (2012) examined groups of wells associated with relatively mature fields and concluded the different well groups exhibited a variety of optimal designs. They found, as of the first quarter of 2012, numerous instances where the large number of fracture stages applied to horizontal hydraulically fractured wells could not be justified economically.…”
Section: Previous Studies On Bakken Well Productivitymentioning
confidence: 99%
“…Engineering studies focused on improving well productivity by adjusting well completion design factors. An early study by Baihly et al (2012) examined groups of wells associated with relatively mature fields and concluded the different well groups exhibited a variety of optimal designs. They found, as of the first quarter of 2012, numerous instances where the large number of fracture stages applied to horizontal hydraulically fractured wells could not be justified economically.…”
Section: Previous Studies On Bakken Well Productivitymentioning
confidence: 99%
“…Although the production is encouraging, intractable problems are also apparent. One of the problems is the fast decline of production in individual producers during depletion development, forcing operators to refracture existing wells or drill new wells [4]. In order to maintain the production rate, it is essential to establish e cient ooding systems for reservoir energy supplement and enhancing oil recovery [5].…”
Section: Introductionmentioning
confidence: 99%
“…We show that each favorable legacy lease held by a private firm leads to a reduction in frontier activity of of 0.25 percentage points, or about 5 percent of the average difference in frontier shares between public and private firms. More-2 Variation in subterranean rock characteristics across shale formations, such as North Dakota's Bakken, gives rise to risks resulting from variation in fracking efficacy, as discussed in Baihly et al (2012), Jabbari, Zeng et al (2012), and Saputelli et al (2014). See also Gilje (2016) for a discussion on exploratory vs. development drilling.…”
mentioning
confidence: 99%